Hologram imaging quality improvement by ionization controlling based on the self-trapped excitons with double-pulse femtosecond laser - Wang Feifei; Jiang Lan; Pan Changji; Wang Zhipeng; Lian Yiling; Wang Qingsong; Tao Wenpan; Sun Jingya (Nanophotonics)
Holograms hidden inside transparent materials are important for information encryption storage because of their advantages of secrecy, and could completely avoid information loss caused by surface wear. Inside the transparent material, the modified filaments array was need for hologram fabrication to change the optical phase or amplitude of incident laser, which is sensitive to the change of refractive index. Then the uniformity of modified filaments inside transparent materials is highly required. In this study, by tuning the interval time of the double-pulse processing, holograms with improved imaging quality were fabricated by double-pulse femtosecond laser and the effect and mechanism of self-trapped excitons (STEs) on the ablation have been systematically studied. The imaging quality of the hologram fabricated with double-pulse laser was superior to that of the one fabricated with the single-pulse laser and 350 fs was verified to be the best time interval for double-pulse processing. The evolution of the electrons dynamics was investigated by using the pump-probe technology. With the double-pulse time interval increasing, the residual electrons, excitons, STEs, and defects caused by the first sub-pulse would become dominated sequentially. The results demonstrated the controllability of STEs and quality improvement of final structures by double-pulse femtosecond laser processing.